Hindu Religion Teacher Communication Strategy In Instilling The Values Of Religious Moderation - Desak Ketut Angraeni (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
ABSTRACT The communication strategy of Hindu religious teacher in instilling the values ??of religious moderation to students in schools today is really very important because it provides the values ??of Hindu religious teachings such as Widya which is intelligence, whether intellectual, social, or spiritual intelligence. The higher a person's intelligence, the easier it will be to manage a difference. Then there is Maitri that is love. Hindu religious teachers must teach love to others and instill the value of love without looking at the religious differences that are adhered to by each student so that a high sense of brotherhood is created so that it is not easily separated by anyone. Next is Ahimsa, which is the act of not harming other living beings. The Hindu religious teacher must also provide an understanding that hurting other people is not right and is prohibited by any religion. Then the last one is Shanti which means peace. The Hindu religious teacher gives an understanding that with the presence of Widya, Maitri and Ahimsa will create Shanti or a peaceful life for all of us religious people. Even though we live side by side with friends who have different religions it is not a problem because we love each other and are brothers and sisters so that peace is created. These four values ??of religious moderation according to Hinduism can be given by Hindu religious teacher to students in schools by using various communication strategies that adapt to current conditions in schools. The teacher as an innovator or coordinator must provide message ideas that have been well-formed so that the messenger of religious moderation can be well received by students.